2020
DOI: 10.46827/ejes.v7i11.3331
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Its Influence on Vocabulary and Language Learning: A Case Study

Abstract: Social media is a prominent medium of communication and used by all generations. Besides a tool of communication, institutions have integrated social media such as Twitter, Facebook, and YouTube as learning tools to deliver new information and connect with students. The popularity social media gained over the years has become a debate whether social media platforms are effective teaching and learning tool. This study attempts to seek the influence of social media on English vocabulary development among student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The findings of this study are similar to those of Zainal and Rahmat (2020) who found that university students in Malaysia recommended the referred online sites as prominent sources of exercising English vocabulary. The students stated their understanding of the usage of new words and their socio-cultural impact through social media.…”
Section: Discussionsupporting
confidence: 88%
“…The findings of this study are similar to those of Zainal and Rahmat (2020) who found that university students in Malaysia recommended the referred online sites as prominent sources of exercising English vocabulary. The students stated their understanding of the usage of new words and their socio-cultural impact through social media.…”
Section: Discussionsupporting
confidence: 88%
“…The significant association observed between socialization purposes and vocabulary knowledge may be attributed to the greater incentive for sense-making and self-expression. Engaging in online interactions for social connection motivates individuals to actively search for the meaning of unknown words used by their interlocutors (Sivagnanam & Yunus, 2020;Zainal & Rahmat, 2020), leading to deeper language processing, heightened cognitive engagement, and increased linguistic engagement (De Wilde et al, 2022;Zhang et al, 2021). Furthermore, activities for socialization purposes are characterized by their interactive nature and often involve the use of multimodal materials.…”
Section: Differential Relationships Between Purposes Of Informal Digi...mentioning
confidence: 99%
“…Communication and interaction on social media have given rise to a new linguistic norm called internet slang. The overuse of internet slang terms like ROFL (roll on the floor laugh) and LOL (laugh out loud) negatively impact the traditional or formal English language (Zainal & Noor, 2020). Additionally, it is common to see social media users use informal contractions, short words that people use in casual speech.…”
Section: Literature Reviewmentioning
confidence: 99%